2008
DOI: 10.3844/ajassp.2008.1384.1391
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Paddy Farmers towards Sustainable Agricultural Technologies: Case of Haraz Catchments Area in Mazandaran province of Iran

Abstract: Sustainable agriculture has defined and described in many ways. Despite the diversity in conceptualizing sustainable agriculture, there is a consensus on three basic dimensions of the concept, namely, ecological soundness economically viable and socially acceptable. The dimensions of ecological soundness refers to the preservation and improvement of the natural environment. Environmental issues emerge from the human use of natural resources. Farmers' decisions to adopt a new agricultural technology depend on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 15 publications
6
36
0
1
Order By: Relevance
“…On the other hand, the positive variable of area of the cropping land indicates that the larger the land, the higher instability would be. This result is also similar to the findings of Bagheri [25], Cristoiu, Lucena and Caceres [20], but in terms of social participation 56% of the individuals turned out to be poor. Obstacles to sustainable agriculture have negative effect on farms sustainability, and obstacles decrease agricultural sustainability.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, the positive variable of area of the cropping land indicates that the larger the land, the higher instability would be. This result is also similar to the findings of Bagheri [25], Cristoiu, Lucena and Caceres [20], but in terms of social participation 56% of the individuals turned out to be poor. Obstacles to sustainable agriculture have negative effect on farms sustainability, and obstacles decrease agricultural sustainability.…”
Section: Resultssupporting
confidence: 81%
“…In this study, the results indicate that 85% of the lands are private ownership. This result is similar to the findings of Bagheri [25], Souza, Cyphers and Phipp [26], Damghani [27]. On the other hand, the positive variable of area of the cropping land indicates that the larger the land, the higher instability would be.…”
Section: Resultssupporting
confidence: 80%
“…Many studies attempted to measure risk perception in a broader marketing context (Tzeng et al, 2005;Cox, 1967;Bagheri et al, 2008;Roselius, 1971;Taylor, 1974;Greatorex and Mitchell, 1993;Yavas, 2003;Agrawal and Teas, 2002;Tse, 1999) where the risky or uncertain outcome in a purchase decision is that a product does not perform according to perception. Such research focuses on outcomes that are more disappointing than they are threatening to consumer welfare; more to do with a product underperforming than being unsafe.…”
Section: Methodsmentioning
confidence: 99%
“…According Kallas, et al (2009), relevant factors that can influence the decision to convert from conventional to organic farming include: farmer characteristics, farm structure, farm management, exogenous factors, attitudes and opinions. Bagheri et al (2008) found that easy access to chemical fertilizer made negative perception about the application of manures, while educational level had a strong power in predicting of farmers'perception followed by extension participation and Table 5 outlines the relationship between perception and conditions of farmers using multiple regression analysis. Note: ** are statistically significant Table 5 depicts that there was significant associatiom between dependent variable, perception, and independent variables, farming experience and membership in farming group.…”
Section: Factors Affecring Perception On Organic Farming Conceptsmentioning
confidence: 99%
“…Sagay et al (2014) argued that internal factors was the main focus in improving farmers' perception in developing irrigation areas, which the main factor of perception formation was internal factors, followed by external factors. As Bagheri et al (2008) argued that there was significant relationship between perception towards sustainable agricultural technologies and variables consisting of age, educational level, educational discipline, years of experience in agriculture, farmer's cultivated area, sharecropping, diversity of farmer's rice varieties, out of farm income, contact with information sources/channels and extension participation. On the other side, Kallas et al (2009) identify the policy changes that have been more relevant in motivating adoption of organic practices.…”
Section: Introductionmentioning
confidence: 99%